2020
DOI: 10.1021/acsanm.0c01023
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystalline Protrusion-Rich Indium Tin Oxide Nanoparticles with Colloidal Stability in Water for Use in Sustainable Coatings

Abstract: Indium tin oxide (ITO) nanoparticles (NPs) with protrusions on their surfaces have been successfully obtained by solvothermal synthesis under high In3+ and Cl– concentrations. High-resolution transmission electron microscopy (HR-TEM) observations revealed that the ITO NPs with protrusions consisted of not a polycrystalline but a single-crystalline structure. The results suggested that the unique shape was produced by heterogeneous epitaxial nucleation on the growing surfaces of the ITO NPs in the presence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Both water dispersions of C1 and P1 contain no organic dispersants, and the fundamental difference between C1 and P1 is the shape-induced dispersion stability in water over a long period. [41] The SEM images in Figure 5b revealed that the surface state of the C1-based thin lm was totally different from that of the corresponding P1-based thin lm. Rough and porous structures were clearly observed in Figure 5b.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Both water dispersions of C1 and P1 contain no organic dispersants, and the fundamental difference between C1 and P1 is the shape-induced dispersion stability in water over a long period. [41] The SEM images in Figure 5b revealed that the surface state of the C1-based thin lm was totally different from that of the corresponding P1-based thin lm. Rough and porous structures were clearly observed in Figure 5b.…”
Section: Resultsmentioning
confidence: 94%
“…The details of the preparation of C1 and P2 are summarized in the following Methods section (for P1, see ref. 41). Figure 1a (i), (ii), and (iii) shows the X-ray diffraction (XRD) patterns of C1, P1, and P2, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different indium oxide based bulk nanomaterials have been synthesized by solvothermal/hydrothermal method. In this regard, Suzuki et al [54] synthesized indium tin oxide nanoparticles via solvothermal method for sustainable coating application.…”
Section: Solvothermal/hydrothermal Methodsmentioning
confidence: 99%